2012
DOI: 10.1097/ccm.0b013e3182546855
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal ischemia/reperfusion enhances microglial activation and induces cerebral injury and memory dysfunction in rats*

Abstract: These findings indicate that intestinal ischemia/reperfusion-induced intestinal injury can lead to cerebral damage and memory dysfunction partly via microglia activation which further facilitates oxidative injury, inflammatory response, and neuronal cell apoptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
73
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 69 publications
(76 citation statements)
references
References 43 publications
2
73
0
1
Order By: Relevance
“…The model of intestinal I/R was established as previously reported 27. During the study period, body temperature was maintained at 37°C with the aid of a heating blanket.…”
Section: Methodsmentioning
confidence: 99%
“…The model of intestinal I/R was established as previously reported 27. During the study period, body temperature was maintained at 37°C with the aid of a heating blanket.…”
Section: Methodsmentioning
confidence: 99%
“…Animals were anesthetized with sevoflurane and were placed in a supine position with their paws taped to the operating table. The model of intestinal I/R was established as in our previous study (27). Briefly, the small intestine was exteriorized with a 1-cm midline laparotomy, and the superior mesenteric artery (SMA) was identified.…”
Section: Animal Modelmentioning
confidence: 99%
“…One essential step in the progression of brain diseases is neuroinflammation (1), for which proinflammatory cytokines play a central role (2). Recent work has shown that the pathogenesis of neuroinflammation is mediated in part by the release of adenosine or uridine derivatives from the damaged site, involving a family of ionotropic purinergic receptors (P2XRs) with elevated expression (3).…”
mentioning
confidence: 99%